Mold-Templated Inorganic−Organic Hybrid Supraparticles for Codelivery of Drugs - Maina, James; Cui, Jiwei; Bjornmalm, Mattias; Wise, Andrew; Shepherd, Robert; Caruso, Frank (ACS Publications, 2014)
This paper reports a facile and robust moldtemplated technique for the assembly of mesoporous silica (MS) supraparticles and demonstrates their potential as vehicles for codelivery of brain-derived neurotrophic factor (BDNF) and dexamethasone (DEX). The MS supraparticles are assembled using gelatin as a biodegradable adhesive to bind and cross-link the particles. Microfabricated molds made of polydimethylsiloxane are used to control the size and shape of the supraparticles. The obtained mesoporous silica-gelatin hybrid supraparticles (MSG-SPs) are stable in water as well as in organic solvents, such as dimethyl sulfoxide, and efficiently coencapsulate both BDNF and DEX. The MSG-SPs also exhibit sustained release kinetics in simulated physiological conditions (>30 days), making them potential candidates for long-term delivery of therapeutics to the inner ear.
Keywords: Drug Delivery; Neurotrophins; Supraparticles